China beyond China Infrastructuring and Ecologising a New Global Hegemony? - David Tyfield; Fabricio Rodríguez (International Quarterly for Asian Studies, 2022)
Since the call for papers for this Special Issue less than two years ago, the world has faced a stream of existential challenges, with the background drumbeat of environmental catastrophe(s) and geopolitical tensions growing ever louder. At this moment of unprecedented global challenges, it is increasingly apparent that the sphere of international politics and government, to which citizens would turn for action, is itself also displaying a deep crisis of structural dysfunction. The growing influence of China appears to be both a contributing cause and partial effect of the perceived international vacuum of the multilateral action needed to prevent and respond to such a serious moment of planetary crises. The burning question of the age arguably concerns how China will use, expand or lose its remarkable sources of economic, political and technological influence in this system crisis scenario while attempting to stabilise (or at least not upend) its own economic and socio-political conditions in the process. How will China actually go beyond China? And what world – what world order, what planet and nature, what globe-spanning sociotechnical systems – will this singularly important but not yet well-understood phenomenon create? This Special Issue opens up this agenda, presenting a series of insightful papers across a range of empirical sites that illuminate not only that profound change is underway with the (uncertain) rise of China and the global reach of its infrastructural projects amidst planetary phase shift, but also how that is currently unfolding.